Teachers’ socio-emotional skills: tools for peace in school (2019)
The school is the main scenario for the individual’s training and socialization. Student’s imaginaries, realities, subjectivities, and behaviors are reinforced there. Hence, teachers’ role is fundamental because they act as guides and models of interindividual reactions, relationships, and links generated in the school environment. Through them, school is shaped as a scenario that enables classroom management as a space where students can learn to experience peace. The article is presented as a theoretical review regarding how teachers’ socio-emotional skills affect the management of peace environments in the school, taking into account factors such as classroom climate, school conflict, culture of peace and interpersonal relationships, both between teachers and between teachers and students.